Cure models with exponentiated Weibull exponential distribution for the analysis of melanoma patients - Mohamed Elamin Omer, Mohamed Elamin Abdallah; Abu Bakar, Mohd Rizam; Adam, Mohd Bakri; Mustafa, Mohd Shafie (Multidisciplinary Digital Publishing Institute, 2020)
In the survival data analysis, commonly, it is presumed that all study subjects will eventually have the event of concern. Nonetheless, it tends to be unequivocally expected that a fraction of these subjects will never expose to the event of interest. The cure rate models are usually used to model this type of data. In this paper, we introduced a maximum likelihood estimates analysis for the four-parameter exponentiated Weibull exponential (EWE) distribution in the existence of cured subjects, censored observations, and predictors. Aiming to include the fraction of unsusceptible (cured) individuals in the analysis, a mixture cure model, and two non-mixture cure models—bounded cumulative hazard model, and geometric non-mixture model with EWE distribution—are proposed. The mixture cure model provides a better fit to real data from a Melanoma clinical trial compared to the other two non-mixture cure models.